Reasons Why it (Information Technology) is Essential in Education - Hamrayev Javlonbek Hoshim o’g’li (Genius Publishing Group, 2022)
It is known that the use of modern information technologies in education is one of the priority areas today. As technology advances, the role of the teacher becomes more important. However, this does not diminish the role of the teacher in education and does not exclude him. One of the key factors in the learning process is connecting these students' knowledge with more practice
Keywords: Method; Technology; Histogram; Plot